Acute Pancreatitis in Celiac Disease: Has the Inpatient Prevalence Changed and Is It Associated With Worse Outcomes?. Issue 9 (October 2020) - Osagiede, Osayande; Lukens, Frank J.; Wijarnpreecha, Karn; Corral, Juan E.; Raimondo, Massimo; Kröner, Paul T.
Abstract : Objectives: Studies suggest that adults diagnosed with celiac disease (CD) are at higher risk of developing acute pancreatitis (AP). The aim of this study is to explore the relationship between CD and AP in terms of inpatient prevalence, mortality, morbidity, and resource utilization in the past decade. Methods: Retrospective cohort study using the Nationwide Inpatient Sample (2007–2016). The primary outcome was the occurrence of AP in CD patients. Secondary outcomes were the trend in AP cases in CD patients, and mortality, morbidity, length of stay, and total hospital charges and costs. Results: Of 337, 201 CD patients identified, 7372 also had AP. The mean age was 53 years, 71% were women. The inpatient prevalence of AP in CD was 2.2% versus 1.2% in non-CD cohort ( P < 0.01). Patients with CD displayed increased odds of having AP (adjusted odds ratio, 1.92; P < 0.01). Patients with AP and CD displayed lower odds of morbidity and mortality than non-CD patients with AP. Conclusions: The inpatient prevalence of AP is higher in CD patients, and increased from 2007 to 2016. Patients with CD and AP displayed lower morbidity and mortality, which may suggest that they have a less severe form of AP or lower baseline comorbidity. Abstract : Supplemental digital content is available in the text.